Plant- and animal-protein diets in relation to sociodemographic drivers, quality, and cost: findings from the Seattle Obesity Study. Issue 2 (7th June 2019) - Aggarwal, Anju; Drewnowski, Adam
ABSTRACT: Background: Promoting plant-based proteins is at the forefront of many initiatives in public health nutrition. Objectives: The aim of this study was to characterize the sociodemographic drivers of plant-based protein diet consumption, and to study these in relation to diet quality and cost. Methods: The Seattle Obesity Study series (SOS I and II) yielded the study sample ( n = 1636). Sociodemographic data were obtained by survey self-report. Diet quality and cost came from the Fred Hutchinson Cancer Research Center Food-Frequency Questionnaire linked to retail food prices. The Healthy Eating Index 2010 (HEI-2010) and mean adequacy ratio (MAR) served as measures of diet quality. Linear regressions with robust standard errors examined associations. Results: Total proteins contributed 16.8% of daily dietary energy. The breakdown by animal and plant proteins was 10.9% and 5.9%, respectively. The sociodemographic factors associated with plant-protein consumption were a positive attitude towards healthy eating and higher education but not income. Plant-protein diets were characterized by severalfold increases in nuts and seeds, soy and legumes, but much less meat, poultry, dairy, solid fats, and added sugars. Higher quartiles of plant-based diets were associated with significantly higher HEI-2010 (β: 13.0 from quartile 1 to quartile 4; 95% CI: 11.8, 14.3) and higher MAR (β: 6.0; 95% CI: 3.5, 8.5) with minimal impact on diet costs (β: 0.35; 95% CI: 0.04, 0.67). In contrast, higher quartiles of animal-protein diets were associated with higher diet costs (β: 1.07; 95% CI: 0.77, 1.36) but lower HEI-2010 (β: −3.2; 95% CI: −4.5, −1.9). Each additional 3% of energy from plant proteins was associated with an 8.4-unit increase in HEI-2010 (95% CI: 7.6, 9.1) and with a 4.1-unit increase in MAR (95% CI: 2.7, 5.5) with a minimal increase in diet cost (β: 0.28; 95% CI: 0.06, 0.50). Conclusion: Plant-based protein diets may be a cost-effective way to improve diet quality at all levels of income. Future research needs to evaluate the quality of plant-based protein in relation to amino acids and health.